Microchemical and Microstructural Analysis of Major and Accessory Minerals During Fluid-Rock Interactions and Deformation - Prent, Alexander Martijn (Curtin University, 2019)
In order to improve our understanding of the relation between fluid-rock interactions and deformation, deep crustal rocks that show evidence of hydration reactions have been analyzed, using microchemical and microstructural analysis techniques. Monazite from the Reynolds Range, proved capable of recording hydrous melt evolution. The combination of monazite and apatite determined timing of shear zone activity in central Australia and the analyses of pyroxene showed its recrystallization was dependent on the fluid flux present.